2004
DOI: 10.1590/s0034-89102004000200018
|View full text |Cite
|
Sign up to set email alerts
|

Uso de drogas psicotrópicas por estudantes: prevalência e fatores sociais associados

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
57

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 10 publications
2
33
1
57
Order By: Relevance
“…12 This was not observed in the present study in the association found between alcohol abuse/dependence and the occurrence of common mental disorders assessed by the SRQ-20. However, as other studies in the literature, 12,22 the present study found strong association between the use of alcohol and illicit drugs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…12 This was not observed in the present study in the association found between alcohol abuse/dependence and the occurrence of common mental disorders assessed by the SRQ-20. However, as other studies in the literature, 12,22 the present study found strong association between the use of alcohol and illicit drugs.…”
Section: Discussionsupporting
confidence: 83%
“…A study carried out among junior high, and high school students attending public and private schools in Campinas found that 11.9% of the students had consumed alcohol in at least 20 of the 30 days preceding the survey. 22 A survey conducted in 10 Brazilian capitals found that the frequent use of alcohol (six or more times per month) in students aged 10 to 18 years increased from 9.2%, in 1987, to 15%, in 1997. 9 Although the literature points out that single, divorced, or widowed people generally consume more alcohol, 2,11,17,25 the present study did not fi nd any association between marital status and alcoholism.…”
Section: Discussionmentioning
confidence: 99%
“…Literature demonstrates that the performance of family activities, such as talking, going out together and having meals constitute protective factors that reduce risk behaviors 13 . The importance of the positive relationship between parents has been documented for the reduction of risks, such as juvenile delinquency, depression and psychosomatic symptoms 26 . Therefore, "having meals with parents" protects against risk behaviors, such as smoking, drinking and using drugs 2 .…”
Section: Discussionmentioning
confidence: 99%
“…O uso freqüente de álcool (11,7%) encontrado neste estudo corrobora com os achados de Tavares et al (2001), que detectaram uma prevalência de 16,8% em um estudo com adolescentes escolares. Dos 179 universitários pesquisados, 6,2% relataram fazer uso pesado de álcool, dado divergente dos encontrados por Soldera et al (2004), que obtiveram a prevalência de 11,9% entre escolares, mas semelhante ao de Carvalho et al (2000), que encontraram prevalência de 6,5% entre universitários de ciências jurídicas e econômicas. Tais resultados são preocupantes, visto que o uso pesado de ál-cool pode levar a instalação da dependência.…”
Section: Artigo Originalunclassified